2004
DOI: 10.1038/labinvest.3700121
|View full text |Cite
|
Sign up to set email alerts
|

Glial cell expression of hepatocyte growth factor in vitreoretinal proliferative disease

Abstract: The hepatocyte growth factor (HGF) has been crucially implicated in the development of proliferative retinal diseases; however, it is unclear whether retinal glial cells express or respond to HGF. Therefore, we examined the expression of HGF and of the receptor for HGF, c-Met, by immunohistochemical costaining with glial fibrillary acidic protein (GFAP) in epiretinal membranes of patients with proliferative vitreoretinopathy (PVR) and proliferative diabetic retinopathy (PDR), respectively. Furthermore, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 26 publications
0
23
0
Order By: Relevance
“…29 It was recently reported that glial cells in epiretinal membranes express both HGF and its receptor, c-Met. 24 The results from this study reveal that the coexpression of HGF and glial is far more frequent than with RPE cells at all stages of PVR. Furthermore, the overall HGF expression peaks during mid stage PVR when glia numbers appear relatively low (Figure 2).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…29 It was recently reported that glial cells in epiretinal membranes express both HGF and its receptor, c-Met. 24 The results from this study reveal that the coexpression of HGF and glial is far more frequent than with RPE cells at all stages of PVR. Furthermore, the overall HGF expression peaks during mid stage PVR when glia numbers appear relatively low (Figure 2).…”
Section: Discussionmentioning
confidence: 62%
“…22 HGF is a pleiotropic growth factor that has mitogenic, morphogenic, and motogenic activities when cultured with epithelial cells and glial cells. 5,6,14,15,[23][24][25] It has been reported that HGF, a glycoprotein that mediates epithelial-mesenchymal interactions in many tissues, [26][27][28] has autocrine-paracrine activity in RPE 15 and is a major regulator of RPE barrier function. 29 It was recently reported that glial cells in epiretinal membranes express both HGF and its receptor, c-Met.…”
Section: Discussionmentioning
confidence: 99%
“…In epiretinal membranes of patients with PVR or PDR, immunoreactivities for HGF and for the receptor of HGF, c-Met, are expressed by various cell types, including glial and pigment epithelial cells [120,122,123]. HGF stimulates the chemotaxis (but not proliferation) of cultured Müller cells, and promotes the secretion of VEGF [120]. Blood serum and bFGF increase the secretion of HGF from Müller cells [120].…”
Section: Factors Involved In Müller Cell Gliosis and Proliferationmentioning
confidence: 99%
“…HGF is expressed in the inner retina within 24 hours of ischemia-reperfusion, probably by Müller cells [119], suggesting a role of this factor in the early response of the cells to ischemic/hypoxic insults. Neuroretinas of patients with PVR (but apparently not control retinas) express HGF [45,120]. HGF is elevated in the vitreous of patients with PDR [121].…”
Section: Factors Involved In Müller Cell Gliosis and Proliferationmentioning
confidence: 99%
“…2,4,[11][12][13][14] Expression of HGF and Met are associated with tumor progression. 3,4,15,16 In other types of malignant cells, downstream events induced by HGF signaling have been shown to include increased glycolysis 17 and phoshorylation of AnxI.…”
Section: Discussionmentioning
confidence: 99%